Alkalinization of phosphorylase kinase-deficient muscle during tetanic contraction. Issue 2 (February 1981) - Lutaya, G.; Rahim, Z. H. A.; Shuttlewood, R. J.; Bashford, C. L.; Griffiths, J. R.
Abstract : The intracellular pH of resting and stimulated muscle was monitored by two independent methods: measurement of pH iniodacetate-treated homogenates of freezeclamped tissue and the absorbance at 550–443 nm of intracellular neutral red dye in vivo. During tetanic stimulation, muscle of phosphorylase kinase-deficient mice shows a transient alkalinization whereas muscle in normal mice becomes more acid under similar conditions. The alkalinization appears to be caused by abnormally rapid AMP deamination associated with adaptation to phosphorylase kinase deficiency.